2010
DOI: 10.1152/ajplung.00394.2009
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory stimulation and hypoxia cooperatively activate HIF-1α in bronchial epithelial cells: involvement of PI3K and NF-κB

Abstract: The transcription factor hypoxia-inducible factor (HIF)-1 plays a central physiological role in oxygen and energy homeostasis, and is activated during hypoxia by stabilization of the subunit HIF-1α. Recent studies have demonstrated that non-hypoxic stimuli can also activate HIF-1α in a cell-specific manner. Here, we demonstrate that stimulation of BEAS-2B cells and primary human bronchial epithelial cells by proinflammatory cytokines TNFα/IL-4 strongly induced expression and transcriptional activity of HIF-1α … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 54 publications
(63 reference statements)
6
41
0
Order By: Relevance
“…Whereas tissue hypoxia is associated with protein stabilization and increased half-life, normoxic activation occurs via increased HIF-1α protein synthesis or its modification [11,23,24]. For example, it has been demonstrated that stimulation of primary HBECs by pro-inflammatory cytokines TNFα/IL-4 induces expression and transcriptional activity of HIF-1α under normoxic condition and amplifies HIF-1α activation in hypoxia [22]. Since the inflammatory microenvironment in COPD is enriched with cytokines and pro-inflammatory mediators [29], this could be another mechanism of HIF-1α stabilization/activation in COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas tissue hypoxia is associated with protein stabilization and increased half-life, normoxic activation occurs via increased HIF-1α protein synthesis or its modification [11,23,24]. For example, it has been demonstrated that stimulation of primary HBECs by pro-inflammatory cytokines TNFα/IL-4 induces expression and transcriptional activity of HIF-1α under normoxic condition and amplifies HIF-1α activation in hypoxia [22]. Since the inflammatory microenvironment in COPD is enriched with cytokines and pro-inflammatory mediators [29], this could be another mechanism of HIF-1α stabilization/activation in COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Real-time quantitative PCR estimation of the mRNA levels was performed as previously described [21] . Briefly, total RNA was prepared from the lung tissue using RNeasy (Qiagen, Shanghai, China), and cDNA was synthesized using the highcapacity cDNA reverse transcription kit (Applied Biosystems, Carlsbad, CA, USA) according to the manufacturer's protocols.…”
Section: Real-time Quantitative Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
“…Western blotting assays were performed as we have described previously [21] . The intensity of each band was quantified using Quantity One-4.2.3 software (Bio-Rad, Hercules, CA, USA) and normalized relative to the total level of p42/p44 by density analysis.…”
Section: Western Blotting Assaymentioning
confidence: 99%
“…Elevated inflammatory cytokines [e.g., interleukin-1␤ (IL-1␤) and tumor necrosis factor (TNF-␣)], prostaglandin E 2 (PGE 2 ), placental growth factor (PIGF), nuclear factor-B (NF-B) activation, and oxidants are implicated not only in inflammatory pathophysiology of human SCD and transgenic sickle mice, but also in HIF-1␣ activation (11,31,33,38,44,47,55,60). Among the sources of oxidative stress in SCD and transgenic sickle mice are reperfusion injury, plasma membrane NADPH oxidase (59), increased plasma xanthine oxidase (2), endothelial NO synthase (eNOS) decoupling (28), hemoglobin autoxidation (23), and decreased bioavailability of NO (48).…”
mentioning
confidence: 99%